Computation of risk assessment modelling - Makita, K.; Kouamé-Sina, S.M.; Lindahl, Johanna F.; Desissa, F. (Elsevier, 2019)
The demand for risk assessment to evaluate the safety of foods is increasing in low and middle income countries, but almost no textbook on risk assessment modelling for informal market is available. This chapter introduces practical steps for the risk assessors to tackle with such a situation.